Design, Synthesis, Investigation, and Application of a Macromolecule Photoswitch - Pang, Juan; Gao, Ziyu; Tan, Huaping; Mao, Xincheng; Wang, Huiming; Hu, Xiaohong (Frontiers in Chemistry, 2019)
Azobenzenes (AZO) had attracted increasingly interest due to reversible structural change upon UV light. However, poor fatigue durability and photobleaching phenomenon restricted their further applications. Herein, AZO domain as a side chain was incorporated into copolymers, which was synthesized by radical copolymerization in the research. Structure-properties of synthesized copolymer could be adjusted by monomer ratios. Emphatically, responsive properties of copolymer were investigated in different solutions. In DMSO solution, copolymer exhibited effective structural change, stable rapid responsive time (1 min) upon UV light at room temperature, stable relative acceptable recovery time (100 min) upon white light at room temperature, and good fatigue resistance property. In aqueous solution, even more controllable responsive property and fatigue resistance property for copolymer were verified by results. More pervasively, recovery process could be controlled by light density and temperature. In order to clarify reasons for the difference between AZO molecule and AZO side chain, energy barrier or interactions between single atom or even structural unit was calculated by density functional theory (DFT). Furthermore, the status of copolymer was characterized by dynamic light scattering (DLS) and transmission electron microscope (TEM). Finally, copolymer was further functionalized with bioactive protein (ConA) for reducing the cytotoxicity of AZO molecule.